Hydrogen-bonds structure in poly(2-hydroxyethyl methacrylate) studied by temperature-dependent infrared spectroscopy - Morita, Shigeaki (Frontiers in Chemistry, 2014)
Hydrogen-bonds structure in poly(2-hydroxyethyl methacrylate) (PHEMA) were investigated by means of temperature-dependent infrared (IR) spectroscopy. Spectral variations involved with the OH•••OH and C=O•••HO types of hydrogen-bonds were found around the glass transition temperature of 80 °C. Hydrogen-bonds among the hydroxyl groups gradually dissociate with increasing temperature. In contrast, discontinuous variation in the carbonyl bands was observed around the glass transition temperature. An association of the C=O•••HO type of hydrogen-bond with increasing temperature above the glass transition temperature was revealed. These were concluded from the present study that hydrogen-bonds among the hydroxyl groups in each side chain terminal suppress the main chain mobility in the polymer matrix below the glass transition temperature, while the dissociation of the OH•••OH type of hydrogen-bonds induces the association of the C=O•••HO type of hydrogen-bond. As a result, the mobility of the main chain is induced by the change in hydrogen-bonds structure at the glass transition temperature.